The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.2165/00002018-199309020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity Associated with Salicylates

Abstract: Aspirin, the prototype of the salicylates, is a ubiquitous agent. The availability of aspirin, other salicylates and nonsteroidal anti-inflammatory drugs (NSAIDs) as prescription and over-the-counter medications means there is a wealth of clinical experience with these agents. Among the documented adverse effects of aspirin is the potential for ototoxicity. Tinnitus and hearing loss, usually reversible, are associated with acute intoxication and long term administration of salicylates. A range of measured seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 31 publications
1
34
0
2
Order By: Relevance
“…A range of measured serum concentrations of salicylates are reported as correlating with documented ototoxicity (19.6 to >67 mg/dL). Localized drug accumulation and vasoconstriction in auditory microvasculature may be mediated by the antiprostaglandin activity of these agents [20].…”
Section: Opinion Statementmentioning
confidence: 99%
“…A range of measured serum concentrations of salicylates are reported as correlating with documented ototoxicity (19.6 to >67 mg/dL). Localized drug accumulation and vasoconstriction in auditory microvasculature may be mediated by the antiprostaglandin activity of these agents [20].…”
Section: Opinion Statementmentioning
confidence: 99%
“…Tinnitus, a common side effect of high doses of salicylates, has been suggested by some to be due to inhibition of COX-1-dependent synthesis of PGEs by cells of the inner ear. Although conclusive data for this assertion are lacking, several studies have demonstrated the usefulness of PGE 1 analog misoprostal as a therapy for tinnitus [25,26]. Finally, most NSAIDS including aspirin promote salt and water retention, especially when heart or liver disease compromises renal blood flow.…”
Section: Toxic Effects Of Aspirin: the Cox-2 Hypothesismentioning
confidence: 99%
“…Because high doses of salicylate induce tinnitus in humans (Brien, 1993;Day et al, 1989;McFadden et al, 1984;Myers and Bernstein, 1965) in a predictable, dose dependent manner, many animal studies have used sodium salicylate to investigate the behavioral manifestation of tinnitus (Guitton et al, 2003;Jastreboff et al, 1988;Lobarinas et al, in press). The minimum dose needed to induce tinnitus in rats is on the order of 150 mg/kg (Jastreboff and Brennan, 1994;Lobarinas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%